Risk factors for early morbidity and mortality following pancreatoduodenectomy with concomitant vascular reconstruction. (August 2021) - Lim, Tiffany Y.; Leitman, I. Michael
Abstract: Background: Locally advanced pancreatic tumors may require vascular reconstruction for complete resection. However, pancreatoduodenectomy with vascular resection (PDVR) remains a subject of debate due to increased complications. Methods: Patients were identified using the ACS NSQIP Participant User Data Files from 2014 to 2019. Results: The 30-day mortality rate was 2.7%; major complications occurred in 32.2%. There is an increasing trend of PDVR in patients requiring pancreatectomy. There were no significant differences in mortality between PDVR with vein, artery, or venous and arterial resections. High BMI and postoperative biliary stent were risk factors for early complications. High BMI and COPD increased risk of early mortality. Chemotherapy and chemoradiotherapy were negative predictors for early morbidities and mortality, respectively. Conclusion: This study identifies the predictors of early morbidity and mortality in PDVR. The results of this study may assist decision making in perioperative management to optimize overall survival and guide additional research. Highlights: Pancreaticoduodenectomy with concomitant vascular reconstruction (PDVR) for carcinoma is increasing in frequency for locally advanced pancreatic neoplasms. Early morbidity and mortality rates are acceptable. Patients with elevated body mass index (BMI) and underlying COPD have a higher mortality. Elevated BMI and preoperative biliary stenting are associated with a higher incidence of early complications. Neoadjuvant chemotherapy and chemoradiation may also improve resectability and post-operative outcomes.